PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI PEMODERASI (Studi Kasus pada OPD Kabupaten Wonogiri) - Rosa, Cindy Alfira; Rispantyo, Rispantyo; Kristianto, Djoko (Universitas Slamet Riyadi, 2021)
This study aims to determine the effect of human resource competencies onthe quality of local government financial reports and the influence of internalcontrol systems in moderating the relationship between human resourcecompetencies on the qualiy of local government financial statements in OPDWonogiri Regency. This research is a quantitative study using primary data. Thesampling technique uses purposive sampling technique. Data analysis techniqueused is simple linear regression with moderating variable testing using MRA(Moderated Regression Analysis) with absolute difference value testing and dataprocessing using SPSS 23. The results show that human resource competency hasa positive and significant effect on the quality of local government financialstatement. The results of the moderation regression analysis with the absolutedifference value test indicate that the internal control system is not able tomoderate and strengthen the relationship of human resource competencies to thequality of local government financial reports.